Influence of learning and growth toward internal business processes: case studies on Departement of Hospital Pharmacy in DIY - ., Satibi; Fudholi, Achmad; Kusnanto, Hari; ., Jogiyanto (Indonesian Journal of Pharmacy, 2011)
Hospital Pharmacy have revenue contribution to the Hospital reached 40-60%,  thus  becoming  one  of  the  hospital  revenue  center.  However  hospital pharmacy  services  in  Indonesia  are  still  many  shortcomings,  is  considering several  constraints  such  as  the  ability  of  pharmaceutical  workers,  the  limited ability  of  hospital  management,  hospital  management policies,  and  limited knowledge of the relevant parties of hospital pharmacy services. Such conditions must be efforts to change with the development of learning and growth factors, because  these  factors  (human  capital,  organizational  capital  and  information capital)  and  that  effective  management  is  a  source  of  sustainable  competitive advantage. The research objective is to determine the relationship and influence of learning and growth to the internal business processes in Hospital Pharmacy. Kind  of  research  is  non-experimental  research  is  associative.  Research  tool includes a questionnaire indicators of learning andgrowth, and internal business processes.  The  subjects  was  the  head  of  hospital  pharmacy  in  the  hospital region  of  Daerah  Istimewa  Yogyakarta  (DIY).  Sample  size  was  35  hospital.  In addition  to  sending  questionnaires,  random  interviews  will  be  conducted  on several  hospital  pharmacies  to  enrich  the  results  of  the  survey  questionnaire. The  data  was  analyzed  by  correlation  and  linear  regression  to  determine  the relationship  and  influence  the  learning  and  growth  factors  to  the  internal business  processes  in  hospital  pharmacy.  Results  obtained  from  statistical calculations  with  95%  confidence  show  that  there  is a  strong  relationship between  the  organizational  culture  against  internal business  processes  with  r value of 0.981 with a contribution of 96.20% of theorganizational capital of the sustainability  of  the  internal  business  processes  in  Hospital  pharmacy  in Yogyakarta  Special  Region.  There  is  not  significant relationship  between  the human  capital  against  internal  business  processes.   There  is  not  significant relationship between the information capital against internal business processesKey words:learning and growth, internal business processes, the hospital pharmacy